Cooperative Assembly of 2D‐MOF Nanoplatelets into Hierarchical Carpets and Tubular Superstructures for Advanced Air Filtration. Issue 22 (29th March 2022) - Schwotzer, Friedrich; Horak, Jacob; Senkovska, Irena; Schade, Elke; Gorelik, Tatiana E.; Wollmann, Philipp; Anh, Mai Lê; Ruck, Michael; Kaiser, Ute; Weidinger, Inez M.; Kaskel, Stefan
Abstract: Clean air is an indispensable prerequisite for human health. The capture of small toxic molecules requires the development of advanced materials for air filtration. Two‐dimensional nanomaterials offer highly accessible surface areas but for real‐world applications their assembly into well‐defined hierarchical mesostructures is essential. DUT‐134(Cu) ([Cu2 (dttc)2 ] n, dttc=dithieno[3, 2‐ b  : 2′, 3′‐ d ]thiophene‐2, 6‐dicarboxylate]) is a metal–organic framework forming platelet‐shaped particles, that can be organized into complex structures, such as millimeter large free‐standing layers (carpets) and tubes. The structured material demonstrates enhanced accessibility of open metal sites and significantly enhanced H2 S adsorption capacity in gas filtering tests compared with traditional bulk analogues. Abstract : A 2D copper‐based metal–organic framework, DUT‐134(Cu), self‐assembles into carpet‐like mesocrystals offering enhanced accessibility of open metal sites for air‐filtration applications.